Research Hotspots and Trend Analysis of Barrier Dam Break Mechanism Based on CiteSpace - LI Yan'ang; HAN Peifeng; HUANG Shijie; YANG Guocheng; GONG Yukai; LIU Rui (Renmin Zhujiang)
To comprehensively evaluate the research status and analyze the research hotspot and development trend of barrier dam break, this paper uses CitsSpace to analyze the number of publications, institutional authors, and keywords of research literature on barrier dam break from 2008 to 2023. The number of publications shows an upward trend, the top three countries in terms of the number of publications are China, Japan, and the United Kingdom, the main research institutions include the University of Chinese Academy of Sciences, Chengdu Institute of Mountain Hazards and Environment, etc., and the main researchers include Zhong Qiming, Peng Ming, etc. Many researchers have summarized basic break stages through physical experiments; Three commonly used mathematical models have produced good results in the simulation of dam break cases. Good results can be obtained by using FLOW-3D software for the three-dimensional simulation of dam break. Research hotspots in recent years focus on the disaster chain of barrier dams, as well as pay attention to soil erosion happening simultaneously. Scholars in China and abroad have made rich achievements in the study of the mechanism of barrier dam break, focusing on the study of the dam break process and the construction of mathematical models. However, it is still necessary to strengthen the team research cooperation, the construction of refined mathematical models, and the study of the interaction mechanism between the break flood and the downstream river bed. The research on the barrier dam break mechanism may concentrate on the construction of refined mathematical models and enter a new rising period.